Pengaruh Kepuasan Kerja dan Stres Kerja Terhadap Turnover Intention Pada Karyawan PT Fuli Semitexjaya - Andre Anggara; Tinjung Desy Nursanti (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2016)
PT Fuli Semitexjaya engaged in textiles that production sarong, fabric, and shirt. The purpose of this study to analyze the influence of job satisfaction and work stress on turnover intention in workers at PT Fuli Semitexjaya. The method used is associative. Techniques of data collection are done by distributing questionnaires to 105 respondents in PT Fuli Semitexjaya. Data were analyzed using simple linear regression and multiple linear regression. The results of this study indicate that job satisfaction and work stress provide significant effect either partially or simultaneously on turnover intention in PT Fuli Semitexjaya.